(untitled) (Theatrum historiae, 2018)
In the present article, the background of two discussions about the origin of Hevra Kaddisha (Jewish funeral brotherhood), which took place in the pages of the journals Allgemeine Zeitung des Judenthums, Die Neuzeit and Oesterreichische Wochenschrift in 1888–1889 and 1891–1893, is revealed. These discourses show that the efforts of the authors, trying to prove the Talmudic origin of this organization, were not only based on the conclusions of their research activity. Therefore, the study tries to find out the reasons and motivations of this claim. Primarily, it comes from the analysis of both discussions, the causes of their origin and their impact on further scientific research on Hevra Kaddisha. To put both of these discussions in a wider context and to uncover the motivations of particular authors, the paper presents the character of all three journals as well as the biographies of the individual authors and their relation to the then philological research concerning the topic of Hevra Kaddisha. Next, the whole question of Hevra Kaddisha is put into the context of the fight between the Jewish orthodoxy and the reform movement, the struggle of the Jewish communities against antiSemitism and also the context of internal contradiction in the movement Wissenschaft des Judentums.